Assessing the Welfare Impacts of Forest Ecosystem Service Management Policies and Their Distributional Rules - Dreoni, Ilda; Utila, Henri; Neil, Clive; Eigenbrod, Felix; Schaafsma, Marije (Frontiers in Forests and Global Change, 2022)
Community based management (CBM) is widely advocated as an effective method for governing and managing ecosystem services (ES). However, the distributional rules and maximum harvesting levels are likely to affect both the effectiveness of CBMs in maintaining ES and the fairness and equity of access to these ES. This article proposes a methodological approach for investigating normative trade-offs involved in CBM of forests, where forest conservation objectives need to be traded off against livelihoods objectives. The study uses remote sensing methods to quantify forest ES supply in Namizimu Forest Reserve in Malawi, and links this to demand for ES within the villages near the reserve. It then investigates how a plausible set of CBM rules can be developed to cap consumption of forest products to sustainable amount and quantifies, by using monetary valuation techniques, how these set of rules may affect the total well-being of local population. Our results demonstrate that, due to the spatial mismatches between demand and supply, the distribution of provisioning ES to the population across the harvesting area is unequal in biophysical terms. The current available stock of forest products is sufficient to cover the current demand, however, it is higher than the mean annual increment indicating that this level of consumption is ecologically unsustainable and will lead to forest degradation as shown under the business-as-usual scenario. We then examined the impact of governance and how CBM rules to allocate forest ES to different social groups (poor and rich) under a co-management regime will affect total societal welfare. We found that the distributional scenario that maximises total societal welfare expressed in monetary terms across the whole harvesting area is the scenario that distributes 40% of biomass to the rich group while the remaining 60% is allocated to the poor group. However, this scenario maximises Willingness to Pay (WTP) at total level but does not maximise WTP in each sub-area of forest but just for those that have a high availability for biomass. This indicates that the distributional rules that maximise total welfare at aggregate level may not maximise welfare at local level where constraints from biomass availability require to restrict further the distribution of forest products. When biomass availability is low, total societal welfare is maximised with distributional rules that distribute more trees to richer. Yet, a policymaker may choose a distributional rule that distribute more trees to the poor on normative grounds and forego the objective of maximising total welfare. In such cases the WTP analysis outlined in this paper can support the policymaker in choosing the distributional rule that minimise trade-offs between efficiency, i.e., maximising total welfare, and livelihoods objectives.